Factors Affecting the Role of Barangay Desk Officer in Handling Complaints at Barangay Batasan Hills Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The section of this study where we discuss the complaints is very informative. Complaints area normal part of life, and we struggle with numerous issues everywhere. The barangay deskofficer stated that their role is to handle both parties' complaints so that both parties canunderstand when an agreement has been reached that would satisfy both parties wherediscussion can take place at the barangay office desk the neighborhood is assured by us Deskofficers are well trained on how to deal with complainants' complaints.
Keywords: Criminology